Metal–Phenolic Network-Directed Coating of Lactobacillus plantarum: A Promising Strategy to Increase Stability - Haoxuan Zhang; Huange Zhang; Hao Zhong (Foods)
Lactobacillus plantarum exhibits probiotic effects, including regulating the balance of the intestinal microbiota and enhancing immune function. However, this strain often experiences viability loss upon ingestion due to harsh conditions within the human digestive tract. This study aimed to evaluate the efficacy of metal–phenol networks (MPNs) fabricated via three polyphenols—tannic acid (TA), tea polyphenol (TP), and anthocyanin (ACN)—combined with Fe(III) coatings in protecting Lactobacillus plantarum during simulated digestion and storage. The results demonstrated that MPNs formed a protective film on the bacterial surface. While TA and ACN inhibited the growth of Lactobacillus plantarum YJ7, TP stimulated proliferation. Within the MPNs system, only Fe(III)-TA exhibited growth-inhibitory effects. Notably, ACN displayed the highest proliferation rate during the initial 2 h, followed by TP between 3 and 4 h. All MPN-coated groups maintained high bacterial viability at 25 °C and −20 °C, with TP-coated bacteria showing the highest viable cell count, followed by TA and ACN. In vitro digestion experiments further revealed that the Fe(III)-ACN group exhibited the strongest resistance to artificial gastric juice. In conclusion, tea polyphenol and anthocyanin demonstrate superior potential for probiotic encapsulation, offering both protective stability during digestion and enhanced viability under storage conditions.